Narrating in audiovisual: Perspectives of victims of the colombian armed conflict on the audiovisual production process (2022)
In Colombia, the audiovisual has been consolidated as a relevant tool for the construction of historical memory and the documentation of actors’ stories within the framework of the armed conflict. Given its importance, this article seeks to show contributions to think about sensitive ways of working in audiovisual products and their possible articulation with psychosocial actions based on the perspectives and experiences of victims of the Colombian armed conflict with experience in audiovisual production processes. For this purpose, discussion groups were held with victims who had some experience in audiovisual production processes. The results point to two general topics, the first one discusses the nature of the audiovisual as a psychosocial intervention, so it must have the corresponding ethical aspects. The second topic has to do with the act of narration and takes into account the effects on the victim who narrates her story out loud, generating a double feeling of confidence and relief; at the same time it highlights the role of the audiovisual as an artifact of memory and the possibility of awakening feelings of empathy and commitment in the audience, with the hope of contributing to the non-repetition of the victimizing facts.